Thermo - Physical Characterization of Shea Butter for Effective Thermal Energy Storage Application in Solar Dryers - Muhammad, Aminu; Umar, Sadik; Kangiwa, Umar Mohammed; Alhaji, Umar Mohammed; Yaro, Haruna; Olatunji, Wasiu Akinola; umar, Ismail (FUDMA Journal of Sciences, 2026)
Traditional solar dryers often face inconsistent drying temperatures during times of low solar irradiation and after dark, negatively impacting drying efficiency and the quality of the dried products. To enhance solar drying methods, there has been a rising interest in integrating thermal energy storage (TES) systems that utilize phase change materials (PCMs). This research analyzed the thermo-physical characteristics of shea butter as a bio-based PCM suited for latent heat thermal energy storage in solar dryers. Differential Scanning Calorimetry (DSC) was used to assess the material’s thermal properties under controlled conditions. Findings showed that shea butter has a latent heat of fusion of 50.36 J/g and a melting temperature ranging from 31.25°C to 40.16°C. Its thermal conductivity, density, and specific heat capacity were measured at 0.25 W/mK, 910 kg/m³, and 2090 J/kgK, respectively. These properties suggest that shea butter is well-suited for drying processes at low and medium temperatures, such as for fish and agricultural products. Additionally, the thermal stability of shea butter falls within the temperature range needed for solar drying. Its renewable, biodegradable, non-toxic nature, along with local availability, reinforces shea butter as an environmentally sustainable alternative to synthetic PCMs. This study uniquely focuses on the locally sourced shea butter, characterizing it using DSC for potential integration into solar dryer thermal energy storage systems in tropical regions, thus providing valuable foundational data for future research.